2001
DOI: 10.1016/s1534-5807(01)00011-9
|View full text |Cite
|
Sign up to set email alerts
|

Eyes Absent Mediates Cross-Talk between Retinal Determination Genes and the Receptor Tyrosine Kinase Signaling Pathway

Abstract: Eyes absent (eya) encodes a member of a network of nuclear transcription factors that promotes eye development in both vertebrates and invertebrates. Despite extensive studies, the molecular mechanisms whereby cell-cell signaling pathways coordinate the function of this retinal determination gene network remain unknown. Here, we report that Drosophila Eya function is positively regulated by mitogen-activated protein kinase (MAPK)-mediated phosphorylation and that this regulation extends to developmental contex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
67
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 54 publications
5
67
2
Order By: Relevance
“…We extended these observations by demonstrating that Eya protein levels are elevated in aop 1 clones behind the furrow (Figure 7, A-H). This finding suggests that in addition to the modification of Eya activity by MAPK phosphorylation (Hsiao et al 2001), the EGFR pathway also regulates the expression levels of the eya transcriptional unit. In addition it appears that So protein levels are also elevated in aop clones ( Figure 7, I-L) suggesting that either EGFR signaling via Aop regulates both so and eya or there is a serial link between these factors.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…We extended these observations by demonstrating that Eya protein levels are elevated in aop 1 clones behind the furrow (Figure 7, A-H). This finding suggests that in addition to the modification of Eya activity by MAPK phosphorylation (Hsiao et al 2001), the EGFR pathway also regulates the expression levels of the eya transcriptional unit. In addition it appears that So protein levels are also elevated in aop clones ( Figure 7, I-L) suggesting that either EGFR signaling via Aop regulates both so and eya or there is a serial link between these factors.…”
Section: Resultsmentioning
confidence: 91%
“…Rather, the network is characterized by a meshwork of interactions that include numerous feedback loops and closed auto regulatory circuits (Kumar 2009). Additionally, several signaling transduction pathways function reiteratively within the network (Chen et al 1999;Baonza and Freeman 2001;Kurata et al 2000;Hsiao et al 2001;Kumar and Moses 2001b,c;Baonza and Freeman 2002;Voas and Rebay 2004). Complicating our understanding of this network is that all of the interactions described to date do not necessarily occur uniformly throughout the eye.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Third, cotranscriptional activity of EYA is positively regulated by phosphorylation by means of MAPK, and because EYA does dephosphorylate itself in vitro, it is possible that phosphatase-negative mutants cannot turn off their activation by MAPK (Hsiao et al, 2001;Tootle et al, 2003). Moreover, EyaD493N, which carries a point mutation disrupting specifically phosphatase activity, did rescue eya mutant flies (Rayapureddi et al, 2003).…”
Section: Overexpression Of Xeya3 Phosphatase-dead Mutant Formsmentioning
confidence: 99%
“…Instead, EYA proteins can physically interact by means of the so-called Eya domain at the C-terminus with dac and so and are thereby considered to regulate transcription of target genes in the context of a multimeric complex (Heanue et al, 1999;Ikeda et al, 2002;Silver et al, 2003;Ozaki et al, 2004). Recently, it has been demonstrated that Eya proteins translocate from the cytoplasm to the nucleus upon phosphorylation of a conserved PXS/TP motif by MAPK (Ohto et al, 1999;Hsiao et al, 2001) and harbor a phosphatase activity (Li et al, 2003;Rayapureddi et al, 2003;Tootle et al, 2003).…”
Section: Introductionmentioning
confidence: 99%